Respiratory rehabilitation techniques for patients with cystic fibrosis: a protocol for a systematic review and network meta-analysis - Xuefeng Chen; Xinyu Wang; Na Lin; Yilong Tang (BMJ Open)
Introduction Cystic fibrosis (CF) is an autosomal recessive genetic disorder caused by mutations in the cystic fibrosis transmembrane conductance regulator (CFTR) gene, primarily affecting the respiratory and digestive systems. Respiratory rehabilitation techniques play a crucial role in managing pulmonary symptoms and maintaining lung function in CF patients. Although various techniques have been developed and applied, there is currently no globally recognised optimal respiratory rehabilitation regimen. This study intends to conduct a network meta-analysis to comprehensively evaluate and compare the effectiveness of different respiratory rehabilitation techniques in CF patients.Methods and analysis The following key electronic bibliographic databases will be searched from inception to September 2024: Medline, Embase, Cochrane Library, Web of Science, CINAHL and Physiotherapy Evidence Database. We will include randomised controlled trials (RCTs) and quasi-RCTs that compare the efficacy of various respiratory rehabilitation techniques in CF patients, such as airway clearance techniques, exercise training and inspiratory muscle training. The primary outcomes will be lung function (forced expiratory volume in 1 s and forced vital capacity) and exercise capacity (VO2 max and 6 min walk test). Secondary outcomes will include quality of life, frequency of pulmonary exacerbations, hospitalisation rates and adverse events. If permitted, data will be synthesised using traditional pairwise meta-analysis and network meta-analysis, with the quality of evidence assessed using the Grading of Recommendations Assessment, Development and Evaluation approach.Ethics and dissemination Ethical approval will not be required for this protocol. The results of the final review will be disseminated via peer-reviewed journals and conference presentations.PROSPERO registration number CRD42024574551.